Lithuanian equivalents of German nominal compounds in an anonymous German-Lithuanian manuscript from the 17th century Lexicon Lithuanicum - Jarmalavičius, Dalius (Vilnius University Open Series, 2022)
This paper analyses Lithuanian equivalents of German nominal compounds in an anonymous bilingual dictionary of the 17th century Lexicon Lithuanicum. 1208 words translated into Lithuanian were used for the analysis of the German compounds. Firstly, the article focuses on the Lithuanian equivalents, which are simple words (simplicias) and word phrases (syntagms), then the German words translated into Lithuanian as derivatives and compound nouns are described. The presented data are compared with the research results of other manuscripts (bilingual dictionaries C and B) from the 17th–18th centuries. According to the research data, the majority of the German nominal compounds recorded in the dictionary were translated into Lithuanian by simple words or syntagms. Almost a half of the German compounds were rendered into Lithuanian as derivatives, very often represented by suffixation. Lithuanian compound nouns, which serve as equivalents of German compounds make up only about 10 percent of the analyzed words, and are usually represented by N+N word-formation type.